Peningkatan Keterampilan Menulis Kalimat Sederhana melalui Model Pembelajaran Kalimat Konsep - Nurul Mutia; Febrianti Yuli Satriyani (Journal of Practice Learning and Educational Development, 2026)
The purpose of this study was to improve simple sentence writing skills using the concept sentence learning model in elementary schools for III grade students at SDN Cipinang Besar Utara 08, East Jakarta. This study was classroom action research. Data collection techniques included interviews, questionnaires, documentation, and tests. In the initial observation, out of 26 students, only 7, or 27%, were able to write simple sentences. In the first cycle, this increased to 15 students, or 58%, who were able to write simple sentences. In the second cycle, this number increased to 92%, or 24 students. Based on these research results, it can be concluded that using the concept sentence learning model can improve narrative writing skills in III grade students at SDN Cipinang Besar Utara 08 East Jakarta.